Broadening your horizon one day at a time: Relationship goals and exciting activities as daily antecedents of relational self-expansion. (June 2020) - Harasymchuk, Cheryl; Muise, Amy; Bacev-Giles, Chantal; Gere, Judith; Impett, Emily A.
Self-expansion in intimate relationships (i.e., broadening one's perspective through engaging in novel, exciting activities with a partner) has been associated with relationship benefits. The goal of this study was to propose a motivational model of self-expansion to understand what prompts people to engage in self-expanding activities in their relationship on a daily basis. We hypothesized that when people report stronger daily approach relationship goals (i.e., goals focused on pursuing growth, intimacy, and rewards), they would report a greater likelihood of engaging in novel, exciting activities that enhance self-expansion and ultimately promote greater satisfaction in romantic relationships. To test our model, we recruited 122 couples for a 3-week daily diary study. In support of our hypotheses, on days when people (or their partners) reported higher than their usual approach relationship goals, they reported higher relational self-expansion, which was due, in part, to a greater likelihood of engaging in novel, exciting activities with the partner. In turn, higher relational self-expansion was associated with higher daily relationship satisfaction. Our findings have implications for understanding what promotes relationship growth on a day-to-day basis and the outcomes of daily approach-oriented relationship goals.